Learned irrelevance and retrospective correlation learning. - Baker, A; Murphy, R; Mehta, R (2003)
In 1973 Mackintosh reported an interference effect that he called learned irrelevance in which exposure to uncorrelated (CS/US) presentation of the unconditional stimulus (US) and the conditioned stimulus (CS) interfered with future Pavlovian conditioning. It has been argued that there is no specific interference effect in learned irrelevance; rather the interference is the sum of independent CS and US exposure effects (CS + US). We review previous research on this question and report two new experiments. We conclude that learned irrelevance is a consequence of a contingency learning and a specific learned irrelevance mechanism. Moreover even the independent exposure controls, used in previous experiments to support the CS and US exposure account, provide support for the correlation learning process.